PENINGKATAN KINERJA GURU MELALUI KEPEMIMPINAN TRANSFORMASIONAL, MOTIVASI KERJA, DISIPLIN KERJA DAN BUDAYA ORGANISASI DI SMK SWASTA SE-KECAMATAN PULOGADUNG, JAKARTA TIMUR - Wijayanto, Budi Prabowo; Utaminingsih, Sri; Masriah, Imas (STKIP Pesisir Selatan, 2025)
Vocational education plays a strategic role in preparing competent human resources to meet job market demands. However, 40% of vocational high school graduates experience a mismatch between their competencies and industry needs, primarily due to teachers' suboptimal performance in aligning the curriculum (link-and-match). This study investigates the simultaneous influence of transformational leadership, work motivation, work discipline, and organizational culture on teacher performance in vocational high schools located in the Pulogadung industrial area, East Jakarta, Indonesia. Using a cross-sectional quantitative design, data were collected from 116 teachers in five accredited vocational high schools through a validated questionnaire with a 5-point Likert scale. Multiple linear regression analysis with classical assumption testing was applied. The findings indicate that all four variables significantly influence teacher performance (p < 0.05), with organizational culture showing the highest relative contribution (standardized β = 0.328, t = 4.567, p < 0.001). The combined model explained 76.9% of the variance in teacher performance (R² = 0.769, F = 89.234, p < 0.001). Transformational leadership (β = 0.245), work motivation (β = 0.278), and work discipline (β = 0.167) also showed significant positive effects..